Investigate the use of electrostatics in fabricating 3D objects according to the principles of additive manufacturing technology - Chiang, Zhi Sheng. (2013)
Additive Manufacturing has been a new trend implemented in various industries recently. It is expected to play a significant role in manufacturing in the coming decades due to the many benefits over conventional manufacturing technique which is by removal of materials. There are many additive methods that have been invented over the years and one particular method using xerography is in the works. There are several obstacles to its implementation and one of it is the usage of electric field on the